Accounting Flows: Income, Funds, and Cash. - Coughlan, John W.; Griffin, Charles H. (The Accounting Review, 1966)
The article reviews the book "Accounting Flows: Income, Funds, and Cash," by Robert K. Jaedicke and Robert T. Sprouse.